Microbiome predators in changing soils - Hu, Shunran; Li, Guixin; Berlinches de Gea, Alejandro; Teunissen, Joliese; Geisen, Stefan; Wilschut, Rutger A.; Schwelm, Arne; Wang, Yuxin (Environmental microbiology, 2023)
Microbiome predators shape the soil microbiome and thereby soil functions. However, this knowledge has been obtained from small‐scale observations in fundamental rather than applied settings and has focused on a few species under ambient conditions. Therefore, there are several unaddressed questions on soil microbiome predators: (1) What is the role of microbiome predators in soil functioning? (2) How does global change affect microbiome predators and their functions? (3) How can microbiome predators be applied in agriculture? We show that there is sufficient evidence for the vital role of microbiome predators in soils and stress that global changes impact their functions, something that urgently needs to be addressed to better understand soil functioning as a whole. We are convinced that there is a potential for the application of microbiome predators in agricultural settings, as they may help to sustainably increase plant growth. Therefore, we plea for more applied research on microbiome predators. By providing a state‐of‐the‐art overview of knowledge on soil microbiome predators, we highlight three research topics to focus on to better understand the general role of microbiome predators in natural and agricultural soils under current and future climate change. This overview will advance and guide future research in this emerging field.